(untitled) (International Journal of Engineering and Computer Science, 2025)
New opportunities for fabricating multilayer printed circuit boards (PCBs) have appeared because of additive manufacturing, thanks to greater flexibility, shorter turnaround times and the ability to make prototypes on demand. The durability and compatibility with electromagnetic fields of 3D-printed multilayer PCBs are still not well understood and raise worries for high-standards applications. This research evaluates both the structural durability and electromagnetic interference properties of PCBs that have been 3D printed from special conductive and dielectric materials. A series of prototype PCBs were put together, printed, tested in tests for strength and electrical characteristics and tested for electromagnetic interference. Tests were completed using both finite elements and electromagnetics to support the experimental results. The research has found that 3D-printed PCBs have good strength and work properly, but they still need to improve in reliability and the effectiveness of shielding against electrical interference. It points out important factors that influence the quality of structural and EMC results and gives suggestions for finding the ideal print parameter and material combination. These results are important for developing highly reliable, manufacturable components for new electronic systems used in aerospace, IoT and wearable electronics.